Residual soil and coco peats mix multilayer bricks of anti-radiation / Norhayati Mohamad Noor ... [et al.] - Mohamad Noor, Norhayati; Narudin, Nur Hashira; Abdullah, Hasnain; Mohamat Kasim, Nazirah; Ahmad, Azizah (2022)
In the current technologically developed countries where industrial technology developments have been focused, new products are constantly being introduced to either replace or enhance the existing products. Technology has always advanced with the purpose of making our lives better and easier. However, the development of technology also increases the possibility of exposure to radiation that affects human health. Therefore, anti-microwave materials are needed to absorb or eliminate electromagnetic radiation to protect human health. In this project, brick walls were designed as anti-microwave materials by using agricultural wastes, which are coco peat as absorbing materials. This project aims to develop anti-microwave multilayer bricks using residual soil and agricultural waste as absorbing materials and partial cement replacement. The absorption performance of the multilayer bricks was measured by using the Naval Research Laboratory (NRL) arch-free space method. The performance of the anti-microwave multilayer bricks was compared with the performance of the commercial clay bricks. The performance was analyzed in the frequency range of 1 to 12GHz at an angle of 0 degrees. The measurement results show that the anti-microwave multilayer brick walls produced a better performance with maximum absorption of -23.4676dB at the frequency 1.7GHz (L-band), while the maximum absorption of commercial clay bricks is -9.6265dB at frequency 1.07GHz (L-band). From the result obtained, this can be concluded that coco peat can be used as an absorbing material in the production of microwave absorbers.